A Bibliographic Study of Drug Abuse Research during last 30 years in Iran - Afarin Rahimi Movaghar; Vandad Sharifi; Mohammad Reza Mohammadi; Ali Farhoudian; Elaheh Sahimi Izadian; Reza Rad Goodarzi; Ali Akbar Nejatisafa; Vaghmeh Mansouri (Research on Addiction, 2009)
In the last decades, the produced science has been significantly increased in the field of drug abuse, globally. The objective of this study was to assess the bibliographic aspects of the science produced in Iran on drug abuse in the last 30 years. All scientific papers published from Iran in a 30-year period (1973-2002) in national as well as international scientific journals were assessed for this study. These papers are indexed in the database for Iranian Mental Health Researches, called IranPsych. The total number of 218 papers on drug and drug abuse were found and assessed by six psychiatrists and psychologists with good inter-rater reliability. About half of these papers were published in the last two years. About half of the papers have been published in the Persian medical journals. One-third have been published in international journals. Overall, 449 authors contributed to the 218 published papers from whom 80 percent had only one paper. Half of the papers were written by only 15 authors (3.3 percent). Most of the authors were Medical Doctors and from Medical Universities. None of the researches was received financial support from pharmacologic industries. This study shows that in recent years, the increase in the publication of the researches conducted on drug abuse has been significant. Nevertheless, according to the high prevalence of drug abuse problem in Iran and improvements in the scientific, as well as executive structures, the whole scientific output is insignificant. The findings guide us to a more systematic approach toward training of researchers and promotion of resaerch in this area. Moreover, more active involvement of social scientists and publication of their research findings are recommended.